2022
DOI: 10.1136/bmjopen-2021-052393
|View full text |Cite
|
Sign up to set email alerts
|

Global prevalence and trends in hypertension and type 2 diabetes mellitus among slum residents: a systematic review and meta-analysis

Abstract: ObjectiveFirst, to obtain regional estimates of prevalence of hypertension and type 2 diabetes in urban slums; and second, to compare these with those in urban and rural areas.DesignSystematic review and meta-analysis.Eligibility criteriaStudies that reported hypertension prevalence using the definition of blood pressure ≥140/90 mm Hg and/or prevalence of type 2 diabetes.Information sourcesOvid MEDLINE, Cochrane CENTRAL and EMBASE from inception to December 2020.Risk of biasTwo authors extracted relevant data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 97 publications
0
12
0
Order By: Relevance
“…hypertensive or have Type 2 Diabetes compared to rural counterparts. 38 However, the burden of hypertension, cancer, and diabetes is estimated to be less compared to non-informal settlement urban residents. 38 Mental health.…”
Section: Covid-19 and Urban Inequalitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…hypertensive or have Type 2 Diabetes compared to rural counterparts. 38 However, the burden of hypertension, cancer, and diabetes is estimated to be less compared to non-informal settlement urban residents. 38 Mental health.…”
Section: Covid-19 and Urban Inequalitiesmentioning
confidence: 99%
“…38 However, the burden of hypertension, cancer, and diabetes is estimated to be less compared to non-informal settlement urban residents. 38 Mental health. While mental health is an important part of health and well-being, it is often ignored in informal settlements.…”
Section: Covid-19 and Urban Inequalitiesmentioning
confidence: 99%
“…When specifically addressing multi-morbidity, the sociodemographic structure has been highlighted as a key determinant, identifying the elderly, female, and socioeconomically deprived people as those particularly vulnerable to chronic conditions and multi-morbidity (9)(10)(11)(12). These conditions, along with individual lifestyles and metabolic risk factors, often promote (among other conditions) hypertension and type-2 diabetes mellitus (13). These two NCDs are currently in the spotlight due to their increasing burden worldwide −422 and 1,278 million for diabetes and hypertension in 2014 and 2019, respectively (14,15), as one of the most frequent modes of multi-morbidity (16,17) fostered by their considerable overlap in terms of risk factors (18, 19).…”
Section: Introductionmentioning
confidence: 99%
“…There is a large body of literature devoted to multi-morbidity following a variety of approaches. For example, Johnston et al ( 20 ) addressed the definition and measurement of multi-morbidity; Prados-Torres et al ( 21 ) and Rajoo et al ( 22 ) identified the most common patterns of disease association; Violán et al ( 23 ) highlighted the importance of socioeconomic status as an aggravating factor in multi-morbidity; and Uthman et al ( 13 ) explored the levels of vulnerability between urban and rural settings. However, the afore mentioned studies were conducted at the individual level, largely disregarding the social environment.…”
Section: Introductionmentioning
confidence: 99%
“…The increasing trend and high burden of hypertension in LMICs is worrisome particularly because most of the limited resources for healthcare spending is allocated to managing infectious disease burden in these countries. The burden of hypertension among slum populations specifically is high and rising [9]. Barriers to blood pressure control exist at various levels.…”
Section: Introductionmentioning
confidence: 99%